TAHLĪL AL MUSYKILᾹT FĪ TA'LĪMI AL LUGAH AL 'ARABIYAH BI AL MADRASAH AL SANAWIYAH AL MA'MALIYAH BI AL JᾹMI'AH AL ISLᾹMIYAH AL HUKŪMIYYAH SŪMATRAH AL SYAMᾹLIYAH MĪDᾹN - Anni Kholilah Siregar; Muhammad Taufiq (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to analyze the problems of Arabic learning for class VII MTS Laboratory UINSU Medan using a descriptive qualitative methodology by making eye teachers: Arabic lessons, students who were randomly selected as research subjects. Of course, having an instrument is very important in a study. The research uses observation, interviews, and documentation as research instruments. The problems found based on research that must be solved in teaching and learning Arabic are linguistic and non-linguistic problems. The linguistic problems found are in the form of 1. Sound 2. Writing, 3. Meaning, 4. Vocabulary, 5. Structural meaning. Regarding non-linguistic problems, namely, 1. Student interest. 2. Method, 3. The system, (4. Environment). The importance of this problem is analyzed because it sees students who are increasingly less interested in learning Arabic, and the quality of learning Arabic is decreasing. Seeing this problem, the researcher considers it essential to be discussed and analyze. Alternative solutions to existing problems are also offered in this paper.